(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
To increase renewable energy output and achieve low carbon footprints for buildings, Building-Integrated Photovoltaic (BIPV) is a promising technology. To alleviate power outages and cut down on emissions of greenhouse gases, this article examines Iraq’s options for utilising renewable energy. Using the present state of renewable energy sources as a starting point, it proposes ways to make the most of them. Moreover, it suggests ways to install building-integrated photovoltaic (BIPV) systems and talks about how their demand is on the rise.